2011
DOI: 10.1371/journal.ppat.1002027
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Neisseria meningitidis in Human Whole Blood and Mutagenesis Studies Identify Virulence Factors Involved in Blood Survival

Abstract: During infection Neisseria meningitidis (Nm) encounters multiple environments within the host, which makes rapid adaptation a crucial factor for meningococcal survival. Despite the importance of invasion into the bloodstream in the meningococcal disease process, little is known about how Nm adapts to permit survival and growth in blood. To address this, we performed a time-course transcriptome analysis using an ex vivo model of human whole blood infection. We observed that Nm alters the expression of ≈30% of O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
163
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 129 publications
(176 citation statements)
references
References 95 publications
(119 reference statements)
12
163
1
Order By: Relevance
“…The infrequency of the nalP deletion suggests that it is disadvantageous for the bacteria and that, in the nalP-negative strain, the function could be compensated by other factors or other mechanisms. This hypothesis recalls the redundancy in fH binding by Nm, where strains lacking fHbp can use NspA to bind fH (13,14) to avoid complement activation on bacterial surface.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…The infrequency of the nalP deletion suggests that it is disadvantageous for the bacteria and that, in the nalP-negative strain, the function could be compensated by other factors or other mechanisms. This hypothesis recalls the redundancy in fH binding by Nm, where strains lacking fHbp can use NspA to bind fH (13,14) to avoid complement activation on bacterial surface.…”
Section: Discussionmentioning
confidence: 81%
“…In a previous study of Nm transcriptome analysis in human blood, we showed that the nalP gene was up-regulated during incubation in human blood and that survival of a nalP deletion mutant (named MCΔnalP) in human blood was impaired (14). To further characterize the NalP phenotype, we…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Surface-exposed Mip-like proteins were also found in the important human pathogens Neisseria gonorrhoeae and N. meningitidis where they mediate persistence in macrophages or improve bacterial survival in the blood, respectively (Echenique-Rivera et al, 2011;Leuzzi et al, 2005). In the caries-associated periodontal pathogen Aggregatibacter actinomycetemcomitans a Mip-like protein was found to be up-regulated in primary isolates.…”
Section: Mip-like Ppiases Of Bacterial Pathogensmentioning
confidence: 99%